Cancer Stem Cell Quiescence and Plasticity as Major Challenges in Cancer Therapy - Wanyin Chen; Jihu Dong; Jacques Haiech; Marie-Claude Kilhoffer; Maria Zeniou (Hindawi Limited, 2016)
Cells with stem-like properties, tumorigenic potential, and treatment-resistant phenotypes have been identified in many human malignancies. Based on the properties they share with nonneoplastic stem cells or their ability to initiate and propagate tumors in vivo, such cells were designated as cancer stem (stem-like) or tumor initiating/propagating cells. Owing to their implication in treatment resistance, cancer stem cells (CSCs) have been the subject of intense investigation in past years. Comprehension of CSCs' intrinsic properties and mechanisms they develop to survive and even enhance their aggressive phenotype within the hostile conditions of the tumor microenvironment has reoriented therapeutic strategies to fight cancer. This report provides selected examples of malignancies in which the presence of CSCs has been evidenced and briefly discusses methods to identify, isolate, and functionally characterize the CSC subpopulation of cancer cells. Relevant biological targets in CSCs, their link to treatment resistance, proposed targeting strategies, and limitations of these approaches are presented. Two major aspects of CSC physiopathology, namely, relative in vivo quiescence and plasticity in response to microenvironmental cues or treatment, are highlighted. Implications of these findings in the context of the development of new therapies are discussed.